Addressing National Spirit Through Rhetorical Analysis in Chairil Anwar's "Diponegoro" Poem - Fitri Aulina Tampubolon; Rosmawaty Harahap (Journal of Aceh Studies, 2024)
Chairil Anwar's poem Diponegoro is a literary work that is full of national spirit. This poem tells the story of Prince Diponegoro's struggle against the Dutch colonizers. Chairil Anwar uses various rhetorical techniques intelligently and effectively to arouse his readers' national spirit. This article aims to analyze the rhetoric used by Chairil Anwar in the poem "Diponegoro" to evoke the spirit of nationality. The author uses the text analysis method. Text analysis is a research method that intends to understand the meaning of the text in depth. The Diponegoro poem will be the focus of the text analysis in this study. Rhetorical analysis in the Diponegoro poem will reveal the deepest meaning of the poem through the description of the use of majas, sentence structure, and diction selection. According to the results of the research on Chairil Anwar's Diponegoro poem, there are various majas in it, such as personification, hyperbole, metaphor, synecdoke totem proparte, metonimia, oxymoron, and sarcasm. The choice of diction is the use of words that are firm and straightforward, the use of words that rhyme, and the use of words full of moral values.